PAIR INTERACTION OF ACTIVE COLLOIDS IN AN EXTERNAL CHEMICAL GRADIENT - Ibrahim, Yahaya; Abddulfatah, Saratu (FUDMA JOURNAL OF SCIENCES, 2022)
We study the pair interaction of chemically isotropic active colloidal particles in an externally imposed chemical gradient. Colloid particles migrate in response to a gradient of chemical solutes (i.e., via the diffusiophoresis mechanism). The particles motion induces fluid flow and distort locally the background chemical concentration field. Using the methods of images, we calculate the phoretic inter-particle interaction between two symmetric active colloids in the presence of an externally applied gradient. We highlight an interesting colloidal dipole that would arise from tuning the surface and chemical activity of the colloids. The colloidal phoretic dipoles share similar properties to the electrostatic dipoles. The inter-particle interaction we obtained is an important component for a large-scale simulation of the active colloid suspension. It may also help towards better understanding of the active systems’ emergent phenomena